Chromosome-scale scaffolds of the fungus gnat genome reveal multi-Mb-scale chromosome-folding interactions, centromeric enrichments of retrotransposons, and candidate telomere sequences - John M. Urban; Susan A. Gerbi; Allan C. Spradling (BMC Genomics)
Abstract Background The lower Dipteran fungus gnat, Bradysia (aka Sciara) coprophila, has compelling chromosome biology. Paternal chromosomes are eliminated during male meiosis I and both maternal X sister chromatids are retained in male meiosis II. Embryos start with three copies of the X chromosome, but 1–2 copies are eliminated from somatic cells as part of sex determination, and one is eliminated in the germline to restore diploidy. In addition, there is gene amplification in larval polytene chromosomes, and the X polytene chromosome folds back on itself mediated by extremely long-range interactions between three loci. These developmentally normal events present opportunities to study chromosome behaviors that are unusual in other systems. Moreover, little is known about the centromeric and telomeric sequences of lower Dipterans in general, and there are recent claims of horizontally-transferred genes in fungus gnats. Overall, there is a pressing need to learn more about the fungus gnat chromosome sequences. Results We produced the first chromosome-scale models of the X and autosomal chromosomes where each somatic chromosome is represented by a single scaffold. Extensive analysis supports the chromosome identity and structural accuracy of the scaffolds, demonstrating they are co-linear with historical polytene maps, consistent with evolutionary expectations, and have accurate centromere positions, chromosome lengths, and copy numbers. The positions of alleged horizontally-transferred genes in the nuclear chromosomes were broadly confirmed by genomic analyses of the chromosome scaffolds using Hi-C and single-molecule long-read datasets. The chromosomal context of repeats shows family-specific biases, such as retrotransposons correlated with the centromeres. Moreover, scaffold termini were enriched with arrays of retrotransposon-related sequence as well as nucleosome-length (~ 175 bp) satellite repeats. Finally, the Hi-C data captured Mb-scale physical interactions on the X chromosome that are seen in polytene spreads, and we characterize these interesting “fold-back regions” at the sequence level for the first time. Conclusions The chromosome scaffolds were shown to be of exceptional quality, including loci harboring horizontally-transferred genes. Repeat analyses demonstrate family-specific biases and telomere repeat candidates. Hi-C analyses revealed the sequences of ultra-long-range interactions on the X chromosome. The chromosome-scale scaffolds pave the way for further studies of the unusual chromosome movements in Bradysia coprophila.